The Effects of IFRS Adoption: Analysis of Existing Literature and Suggestions for Further Research - EL IDRISSI RIOUI , Samia; NIMI , Ismail; BENDDIH , Mbarek (Revue Internationale des Sciences de Gestion, 2024)
This paper conducts a comprehensive review and analysis of the literature pertaining to the economic and financial reporting implications associated with the adoption of IFRS. The primary objective is to provide a precise yet comprehensive understanding, drawing from empirical archival literature, of how the adoption of IFRS has influenced various aspects such as comparability, the relevance of accounting figures to a company's value, earnings management, timely losses recognition, analysts' forecasts, and capital markets. The analysis is based on a thorough examination of 65 published by the accounting journals that make up the Social Sciences Citation Index (SSCI), published between 2009and 2022. The findings suggest that forecast accuracy has improved following the implementation of IFRS. Overall, the reliable studies indicate that the economy operating under the framework of IFRS has experienced favorable outcomes, including increased foreign investment and reduced cost of equity.